Co-Pyrolysis technique between Used Lubricant Oil and HDPE by Activated Zeolite Catalyst - Phetyim, N (Frontiers in Engineering Innovation Research, 2015)
This research studied the optimum temperature for activating zeolite to use as a catalyst in the process of co-pyrolysis of used engine oil and high density polyethylene (HDPE) to offer diesel oil. Pyrolysis temperatures in range of 400-430 °C with catalyst of 0.5 % by weight of reactant and used engine oil per HDPE of the ratio of 100:0 by weight were performed. Zeolite was activated at 200 300 and 400°C. It was found that the optimized activated temperature at 400 °C provided the highest pyrolysis oil of 73.80 wt% while flash point temperature was lower than the standard of Department of Energy Business. Co-pyrolysis in ratio of oil:HDPE of 75:25, 50:50, 40:60, 25:75 and 0:100 by weight were studied. Experimental results showed that only the ratio of 50:50 to oil pyrolysis the qualifying standard diesel, such as flash point of 61.5 °C, specific gravity of 0.820, viscosity of 2.60 cSt, color of 3.0 and distillation of 90% recovered at 250.5 °C. The analysis of component of hydrocarbon by GC-MS of co-pyrolysis oil at the ratio of 50:50 showed the maximum linear paraffin lower than C24 (C<24) and subsequent double bonds contained hydrocarbon compounds.